Recent advancements in targeted protein knockdown technologies-emerging paradigms for targeted therapy - Mansi Joshi; Pranay Dey; Abhijit De (Open Exploration Publishing Inc., 2023)
A generalized therapeutic strategy for various disease conditions, including cancer, is to deplete or inactivate harmful protein targets. Various forms of protein or gene silencing molecules, e.g., small molecule inhibitors, RNA interference (RNAi), and microRNAs (miRNAs) have been used against druggable targets. Over the past few years, targeted protein degradation (TPD) approaches have been developed for direct degradation of candidate proteins. Among the TPD approaches, proteolysis targeting chimeras (PROTACs) have emerged as one of the most promising approaches for the selective elimination of proteins via the ubiquitin-proteasome system. Other than PROTACs, TPD methods with potential therapeutic use include intrabody-mediated protein knockdown and tripartite motif-21 (TRIM-21) mediated TRIM-Away. In this review, protein knockdown approaches, their modes of action, and their advantages over conventional gene knockdown approaches are summarized. In cancers, disease-associated protein functions are often executed by specific post-translational modifications (PTMs). The role of TRIM-Away is highlighted in the direct knockdown of PTM forms of target proteins. Moreover, the application challenges and the prospective clinical use of TPD approaches in various diseases are also discussed.